Efek Pemberian Eugenol Isolat Bunga Cengkeh (Syzygium aromaticum) terhadap Histologi Pankreas Tikus Diabetes - Sinta wahyu utami; I Made Sudarma; Candra Dwipayana Hamdin (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Diabetes mellitus is disease with a high prevalence rate and continuously increase in Indonesia. So some researchers began to glance at natural rescource for prevention and treatment of diabetes mellitus. Clove Flower (Syzygium aromaticum) contains eugenol that can chemically lower blood sugar levels. The aimed of this research is to know the effect of eugenol on pancreas histology of diabetic rats. Clove flowers was extracted used maseration method use n-hexan and eugenol was isolated tested with TLC. Alloxan-induced rats were dosed 125 mg / kg BW IP and then the eugenol was administered in dosage 10 mg / kg BW compared with glibenclamid 1,35 mg /Kg BW orally for 14 days. Observation of pancreatic histology results were made pancreatic preparations using Hematoxilin Eosin (HE) staining. The results showed that alloxan-induced rats had pancreatic cell damage. How ever, after being treated with Glibenclamide and Eugenol showed the improvement of damage organs. Giving the eugenol at a dose of 15 mg / kg BW showed the most significant improvement.